Male Gaze in Indian Cinema: The Presentation of Women in Mainstream Cinema - Roy, Mouparna (International Journal of Humanities and Education Development (IJHED), 2021)
Since the advent of motion pictures, movies have had a great impact on the masses. It has been used as a medium of communication with society as it has been said that movies are the reflection of society. In the Indian context, we can see the depiction of different identities in the cinemas, like gender, queer, ethnic groups and so on (multiculturalism). But the question is how far it is to address the problems of these marginalized sections. Even as a common person, we can notice the less or misrepresentation or misrecognition of the subaltern groups in Indian cinema. One of the most misrepresented among these and the most discussed topic is gender as patriarchy is dominant in almost every society which makes the subjugation of women a global grievance. In the cinematic world, too women have been exploited or oppressed and misrepresented by different means. One of the problems which have been talked about over and over is the concept of ‘male gaze’ (Mulvey, 1975). Women have always been objectified or commodified in the cinemas across the globe. Therefore, the concept of the ‘male gaze’ given by Mulvey addresses the problems of cinemas often being made from the male point of view and the content is specifically made for a heterosexual male. The ‘female-centric’ movies which are claimed by the filmmakers as a way of women's empowerment have also been criticized by the feminists as merely a male standpoint. In this paper, I will try to analyze a few Indian movies and see how much the ‘male gaze’ is persistent in these movies